Flash Mob Impact on Dissemination and Evaluation of Cultural Heritage - Vlaeva, Ivanka (Interdisciplinary Studies in Musicology, 2022)
Flash mob is a newly coined practice which is flourishing in urban spaces in the beginning of the 21st century. Its specific form known as art mob is affirmed as a good means for promotion and dissemination of music and dance as well as for demonstration of ideas and advertisements. In this way art mobs receive new content compared with the initial flash mob forms. Due to the new borderless communications and global mobile networks, flash mobbing became a good opportunity for achieving different goals and conveying special messages, but it is also made for commercial use. Thus, different roles and functions of cultural heritage are shown and cultural symbols are presented through flash mob actions. Also, national memory signs are activated through this practice. The research continues my previous studies on the topic. In this survey further questions arise. In what way is cultural heritage shown in flash mob actions? How does it happen in three different Slavic- speaking countries? Which are the chosen music and dance symbols in flash mobs and what do their messages look like? The main focus of my research is flash mob impact on dissemination and evaluation of cultural heritage through various actions.